Studies of chitosan thionine-reduced graphene oxide nanocomposite as electrode for ganoderma disease biosensor / Muhammad Aidil Ibrahim - Ibrahim, Muhammad Aidil (2019)
Biosensor is a device that applies biological components to detect target substances involving electrochemistry. In this research, DNA-based biosensor was developed to sensitively detect Ganoderma boninense (GB) which is a fungus that causes basal stem rot to oil palm trees. The DNA-based biosensor applies indium-tin-oxide (ITO) coated glass electrode fabricated with materials that enhances the electrochemical properties and the sensitivity of the sensor. The electroconductive reduced graphene oxide (rGO) was used to fabricate ITO electrode as it promotes electroconductivity which allows the sensor to be more sensitive. Another material used, thionine, has a large amount of amino groups to promote immobilization of DNA strands onto the electrode. The composition of thionine with 0.1 mg/mL rGO was successfully determined to induce highest stability to rGO molecules when operating with water-based solvents as thionine makes it more hydrophilic.